(untitled) (Società e diritti, 2023)
The paper focuses on the concept of shared administration, deemed as shared exercise of administrative function both by Public administration and private sector. More specifically, the work analyses Article 55 of the 2017 Third Sector Code, devoted to Public administrations and private sector relationships. Such relationships have been the subject of remarkable studies and of important court decisions (also at constitutional level), but the arguments supporting those views and the grounds of those decisions are not always convincing. Moreover, the study focuses on the legal implications of the shared administration at procedural level.